Mas Receptor Activation Contributes to the Improvement of Nitric Oxide Bioavailability and Vascular Remodeling During Chronic AT1R (Angiotensin Type-1 Receptor) Blockade in Experimental Hypertension. Issue 6 (December 2020) - Savoia, Carmine; Arrabito, Emanuele; Parente, Rosa; Nicoletti, Carmine; Madaro, Luca; Battistoni, Allegra; Filippini, Antonio; Steckelings, Ulrike M.; Touyz, Rhian M.; Volpe, Massimo
Abstract : Angiotensin (1–7) production increases during AT1R (angiotensin type-1 receptor) blockade. The contribution of Ang (1–7) (angiotensin [1–7]) and its receptor (MasR) to the favorable effect of angiotensin receptor blockers on remodeling and function of resistance arteries remains unclear. We sought to determine whether MasR contributes to the improvement of vascular structure and function during chronic AT1R blockade. Spontaneously hypertensive rats were treated with Ang (1–7) or olmesartan ± MasR antagonist A-779, or vehicle, for 14 days. Blood pressure was measured by tail cuff methodology. Mesenteric arteries were dissected and mounted on a pressurized micromyograph to evaluate media-to-lumen ratio (M/L) and endothelial function. Expression of MasR and eNOS (endothelial nitric oxide synthase) was evaluated by immunoblotting, plasma nitrate by colorimetric assay, and reactive oxygen species production by dihydroethidium staining. Independently of blood pressure, olmesartan significantly reduced M/L and improved NO bioavailability, A-779 prevented these effects. Likewise, Ang (1–7) significantly reduced M/L and NO bioavailability. MasR expression was significantly increased by Ang (1–7) as well as by olmesartan, and it was blunted in the presence of A-779. Both Ang (1–7) and olmesartan increased eNOS expression and plasma nitrite which were reduced by A-779. Superoxide generation was attenuated by olmesartan and Ang (1–7) and was blunted in the presence of A-779. These MasR-mediated actions were independent of AT2R activation since olmesartan and Ang (1–7) increased MasR expression and reduced M/L in Ang II (angiotensin II)–infused AT2R knockout mice, independently of blood pressure control. A-779 prevented these effects. Hence, MasR activation may contribute to the favorable effects of AT1R antagonism on NO bioavailability and microvascular remodeling, independently of AT2R activation and blood pressure control. Abstract : Supplemental Digital Content is available in the text.